Territorial competitiveness in the development region South-East. Case study: Buzæau county - Mihai Alexandru Chiţea (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 7th Edition of the International Symposium, November 2016, Bucharest, 2016)
The present paper attempts to evaluate the territorial competitiveness at the level of the development region South-East, of Buzæau county respectively, starting from the premise of the identification of the strengths and weaknesses influencing the specific competitiveness of the investigated units. The paper draws on an evaluation model developed for measuring the local competitiveness in Croatia, which was adapted to Romania's specificities, with regard to the relevance, sources and availability of indicators. The adapted model was used for the evaluation of territorial competitiveness at regional and county level. The working hypothesis was represented by a lower competitiveness level in the case of the county Buzæau, compared to that of the South-East region; this situation is mainly determined by the factors relating to the development level of the non-agricultural business sector, of specialization and innovation.
Keywords: A13; P47; 330; territorial; regional competitiveness; evaluation models; indicators